Effect of Vertical Misfit on Screw Joint Stability of Implant-Supported Crowns - Assunção, Wirley Goncalves [UNESP]; Delben, Juliana Aparecida [UNESP]; Tabata, Lucas Fernando [UNESP]; Ricardo Barao, Valentim Adelino [UNESP]; Gomes, Erica Alves [UNESP] (Springer, 2011)
The passive fit between prosthesis and implant is a relevant factor for screw joint stability and treatment success. The aim of this study was to evaluate the influence of vertical misfit in abutment-implant interface on preload maintenance of retention screw of implant-supported crowns. The crowns were fabricated with different abutments and veneering materials and divided into 5 groups (n = 12): Gold UCLA abutments cast in gold alloy veneered with ceramic (Group I) and resin (Group II), UCLA abutments cast in titanium veneered with ceramic (Group III) and resin (Group IV), and zirconia abutments with ceramic veneering (Group V). The crowns were attached to implants by gold retention screws with 35-N cm insertion torque. Specimens were submitted to mechanical cycling up to 10(6) cycles. Measurements of detorque and vertical misfit in abutment-implant interface were performed before and after mechanical cycling. ANOVA revealed statistically significant difference (P < 0.05) among groups for vertical misfit measured before and after mechanical cycling. The abutments cast in titanium exhibited the highest misfit values. Pearson correlation test did not demonstrate significant correlation (P > 0.05) between vertical misfit and detorque value. It was concluded that vertical misfit did not influence torque maintenance and the abutments cast in titanium exhibited the highest misfit values.
Keywords: casting; material selection; opticalmicroscopy; titanium